The End of Investment Bank Capitalism? An Economic Geography of Financial Jobs and Power. - Wójcik, D (Clark University, 2012)
This article investigates employment patterns, remuneration, and power relations in the U.S. financial sector between 1978 and 2008. It demonstrates that investment banking has played a central part in the securities industry, which has been by far the most expansive segment of the U.S. financial sector and a significant contributor to growing income inequality. The power of investment banking has risen over the past 30 years under the conditions of the growing demand for investment services, technological changes, deregulation, and globalization. Investment banks were at the heart of the shadow banking system, inventing many of the products used by it and often disguising its operation, thus contributing decisively to the outbreak of the global financial crisis of 2007-9. With leading U.S. investment banks converted into bank holding companies and the threat of reregulation, the future of investment banking is uncertain. One area of uncertainty is the banks' relationship with sovereign wealth funds, which involves both opportunities and challenges. The article identifies the economic geography of investment banking as one of the keys to understanding the dynamics of the contemporary world economy and promotes a mesolevel approach to geographies of finance.